Study of Edible Film from Corn Starch (Zea Mays L.) on the Quality of Minimally Processed Jackfruit - Ifmalinda Ifmalinda; Dinah Cherie; Siti Azzahra Kurnia (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Minimally processed jackfruits can usually be found in traditional markets, but the fact found that jackfruit is sold unpackaged and the fruit is not fresh, some have even browned and are infested with flies. Refrigerator is usually applied, but this technology is relatively expensive and not all farmers/traders can afford it. Edible film is an alternative that is easily degraded and decomposed by natural composers plus zinc oxide (ZnO) which is a piezoelectric ceramic that has anti-microbial properties. The purpose of this research was to determine the effect of ZnO concentration on the characteristics of edible films and to determine the best concentration of ZnO and its effect on packaging in jackfruit. Variations in the concentration of ZnO used 0%, 3%, 9% and 12%. Observations on jackfruit were carried out at room temperature. Results showed the higher the concentration of ZnO, the better the ability of edible films with ZnO to maintain the quality and shelf life of jackfruit. Edible film with 12% ZnO was able to extend the shelf life of processed jackfruit for at least 5 days at room temperature . Keywords:  Hardness, Weight loss, Total dissolved solid, Microbial test, Water content.